2019
DOI: 10.3390/en12091686
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Optimization of Exergy Flows inside a Transcritical CO2 Ejector for Refrigeration, Air Conditioning and Heat Pump Cycles

Abstract: In this study, the exergy analysis of a CO2 (R744) two-phase ejector was performed using a 1D model for both single and double choking conditions. The impact of the back pressure on the exergy destruction and exergy efficiencies was presented to evaluate the exergy performance under different working conditions. The results of two exergy performance criteria (transiting exergy efficiency and Grassmann exergy efficiency) were compared for three modes of an ejector functioning: Double choking, single choking and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Many scientific papers presenting results of exergy analysis appear every year in the literature. They concern, for instance, combined cycle power plants [1][2][3][4], steam Rankine cycles [5][6][7][8], organic Rankine cycles [9][10][11][12], refrigeration cycles [13][14][15][16], thermal and PV solar systems [17][18][19][20], fuel cells [21][22][23][24], heat exchangers [25][26][27][28]. Review papers on the exergy analysis of combined cycle power plants [29], steam power plants [30], solar energy applications [31], fuel cells [32], and heat exchangers [33] are available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many scientific papers presenting results of exergy analysis appear every year in the literature. They concern, for instance, combined cycle power plants [1][2][3][4], steam Rankine cycles [5][6][7][8], organic Rankine cycles [9][10][11][12], refrigeration cycles [13][14][15][16], thermal and PV solar systems [17][18][19][20], fuel cells [21][22][23][24], heat exchangers [25][26][27][28]. Review papers on the exergy analysis of combined cycle power plants [29], steam power plants [30], solar energy applications [31], fuel cells [32], and heat exchangers [33] are available.…”
Section: Introductionmentioning
confidence: 99%
“…If one now considers the sequence of the infinitesimal deformations of S that yield the displacement of A from V 1 to V 2 , one obtains equation (13).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the transcritical heat pump cycle, the higher-pressure difference causes higher exergy loss, so choosing the appropriate expansion device is vital. The ejector was introduced as an alternative method to decrease the expansion loss, and it attracts many researchers' attention [3,[7][8][9][10]. Fangtian and Yitai [11] compared the ejector and throttling valve performance in the heat pump cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Sahar Taslimi et al evaluate the system performance of a CO2 two-phase ejector for the HPACS based on Grassmann exergy analysis and transiting exergy analysis. It was concluded that transiting exergy analysis is more suitable for a CO 2 two-phase ejector compared to Grassmann exergy analysis [23]. Honghyun Cho et al conducted an advanced exergy analysis on automotive air conditioning systems with R1234yf refrigerant.…”
Section: Introductionmentioning
confidence: 99%